J. V. Volk-Levanovich and his memories: touches on the portrait of linguist - Maliugin, Oleg I.; Maksimchik, Andrey N. (Journal of the Belarusian State University. History, 2020)
The article is devoted to biography and activities at the Belarusian State University of Slavic philologist Joseph V. VolkLevanovich. On the basis of previously unpublished documents, as well as recent historiography, the text contains unknown details from his biography (studies, military service, family), relations with colleagues at the university, interpretation by J. V. Volk-Levanovich of the causes of the conflict with J. Y. Lesik and other figures of the Belarusian national movement of the 1920s. The documents published in the article (memoirs, diary pages, letters) clearly demonstrate the processes that took place in the scientific and pedagogical and cultural life of Minsk during the period of the policy of Belarusization.
Keywords: J. V. Volk-Levanovich; J. Y. Lesik; memorials; Belarusian State University; linguistics; teaching the Belarusian language